ΣΚΕΨΕΙΣ ΓΙΑ ΤΟΝ ΔΥΙΣΜΟ ΤΗΣ PERFORMANCE [THOUGHTS ABOUT THE DUALISM OF THE PERFORMANCE ] - Pefanis, Giorgos (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The normative function of the performance, as Herbert Marcuse has already described in his «performance principle», always accompanies any radical function of performances, and its power today is evidently dominant. This does not mean, of course, that the transgressive and radical forces of performances have been eliminated. However, the fact remains that the dualism of normative and radical performance pertains to the relations of each performance with its respective historical, political, and economic contexts and therefore has a relative validity. This means that there may be performances without innovative or radical forces, without any transgressive function, or, equally common, performances with seemingly innovative or transgressive elements, which, however, function fundamentally in a normative manner and in complete alignment with the hegemonic discourse and cultural norms: a performative repetition that fundamentally performs the repetition of itself, a performance of the repetition of performance, a performance for the sake of performance and of the norm from which it originates.